Identification of Accident-Prone Points (Black Spots) on the Ujung Gading-Simpang Empat Road Section - Arsyad, Nadra; Leilany, Lili; Pratama, Ihsan (Universitas Negeri Padang, 2024)
The Ujung Gading-Simpang Empat road section has the highest number of accidents in West Pasaman Regency. Accidents that occur at a location range from minor injuries to death. This research aims to determine the main factors influencing accidents, accident characteristics, and black spots and find solutions to minimize accidents. Research method, the method used is a quantitative descriptive method. Driver factors are the biggest factor causing accidents with 330 cases in 2018-2022. Apart from driver factors, vehicle factors also influence traffic accidents with 75 cases in the 2018-2022 period. Analysis of the Highest Accident Rate using the Accident Equivalent Number (AEK) method, and to calculate the number of accidents and the Upper Control Limit (UCL) method to determine accident-prone locations. The data used is the 2018-2022 West Pasaman Traffic Police traffic accident report data which is grouped based on characteristics. Based on the calculation results, the Ujung Gading-Sungai Aur road section has an AEK value of 1081 and UCL 1,036, Sungai Aur-Simpang Tiga Alin with an AEK value of 697 and UCL 884m26, and Simpang Tiga Alin-Simpang Empat with an AEK value of 690 and UCL 840.77. So these three roads are declared as accident-prone areas (black spots). To minimize the number of accidents, efforts are made by law enforcement (Enforcement), education (Education), and engineering (Engineering).